The legal regulation of liability insurance in the ABGB - Karel Schelle (Journal on European History of Law, 2011)
This article deals with the analysis of the legal regulation of liability insurance in the second half of the 19th and the beginning of the 20th century in the Austro-Hungarian Monarchy. A thorough analysis is given to the relevant provisions of the Allgemeines Bürgerliches Gesetzbuch (ABGB) of 1811, the insurance regulations, and the preparatory process leading to the adoption of the Insurance Contract Act.